The role of the KEAP1-NRF2 signaling pathway in form deprivation myopia guinea pigs - Zhiming Gu; Jiayu Meng; Weiqi Zhong; Changjun Lan; Qingqing Tan; Xiaoling Xiang; Hong Zhou; Xuan Liao (BMC Ophthalmology)
Abstract In recent years, the global prevalence of myopia has reached an unprecedented level, especially‌ in East Asia. Multitude of studies has shown that the etiology of myopia is complex. Some researchers have suggested that oxidative stress (OS) may contribute to myopia, although there are limited reports on the alterations of related signaling pathways. Notably, the Kelch-like ECH-associated protein 1 (KEAP1) -nuclear factor erythroid 2-related factor 2 (NRF2), which plays a significant role in regulating OS and the mechanism, has not been explored in myopia. To investigate the modulation of KEAP1-NRF2 signaling pathway and its downstream superoxide dismutase (SOD) during the development of form-deprivation myopia, three-week-old guinea pigs were randomly assigned to four groups: negative control (NC), self-control (SC), form-deprivation myopia (FDM), and FDM group treated with tert-butylhydroquinone (TBHQ). Spherical equivalent (SE) and axial length (AL) were measured by retinoscopy and A-scan ultrasound, respectively. The results revealed that TBHQ treatment decelerated the progression in SE and AL changes. Immunohistochemistry (IHC) assessed the distribution and expression of KEAP1, NRF2, and SOD. The results shown that they located in the retinal ganglion cells (RGC). Subsequently, retinal mRNA and protein expression levels of KEAP1, NRF2, and SOD were quantified using real-time polymerase chain reaction (RT-PCR) and Western blot (WB) analysis. The RT-PCR and WB results demonstrated that TBHQ could activate NRF2, induce KEAP1 degradation, and enhance the expression of the antioxidant SOD. In summary, the modulation of KEAP1-NRF2 and it downstream SOD expression could alter the retinal antioxidant capacity and influence the development of myopia.